The antidote - Sackier, Shelley (HarperTeen, 2019)
"In the world of healers, there is no room for magic. There is only knowledge - precious wisdom, painstaking accounts of herbal remedies, and long-practiced techniques handed down from healer to apprentice since the beginning of time. Fee knows this, just as certainly as she knows that her magic must be kept secret. But the crown prince Xavi, Fee's best friend and only source of comfort, is sick. So sick, and so frustratingly incurable, that Fee can barely contain the magic lying dormant inside her. She could use it, just a little, to heal him. But magic comes at a deadly cost - and attracts those who would seek to snuff it out forever. A wisp of a spell later, Fee finds herself caught in a whirl of secret motivations and dark pasts, where no one is who - or what - they appear to be. And saving her best friend means delving deeper into the lush and treacherous world whose call she's long resisted - and uncovering a secret that will change everything." - Book jacket.